Tomographic Images of Magma Chambers Beneath the Avacha and Koryaksky Volcanoes in Kamchatka. Issue 9 (10th September 2019) - Bushenkova, Natalia; Koulakov, Ivan; Senyukov, Sergey; Gordeev, Evgeny I.; Huang, Hsin‐Hua; El Khrepy, Sami; Al Arifi, Nassir
Abstract: A new tomographic model (Vp, Vs, and Vp/Vs ratio) was built for two neighboring active volcanoes, Avacha and Koryaksky, which represent a serious hazard to the population and infrastructure of Petropavlovsk‐Kamchatsky, the main city of Kamchatka, Russia. Arrival times of seismic P and S waves from almost 5, 000 local events, recorded by a permanent network of seismic stations during 2009–2018, were used for tomography. The resolution of the derived models was carefully tested by a series of synthetic simulations. Prominent anomalies with extremely high Vp/Vs ratios (up to 2.4) were retrieved directly beneath both volcanoes and interpreted as magma reservoirs containing high degrees of partial melt and/or fluids. Beneath Avacha, the upper limit of the anomaly is located at the depth of 2 km below the surface. The reservoir appears to be connected to the surface by a neck‐shaped anomaly of high Vp/Vs ratio associated with active seismicity, which is interpreted as a magma and fluid conduit. Beneath Koryaksky, the magma related anomaly is deeper: Its upper limit is located at a depth of 7 km below the surface. This anomaly is connected with the volcanic cone and is associated with a vertical seismicity cluster, which possibly marks the pathway of fluid ascent and degassing. Between the volcanoes, a 2‐ to 3‐km thick layer of very low Vp and Vs is interpreted as deposits of volcanoclastic sediments. Generally low Vp/Vs ratios in the area between the volcanoes show that the magma reservoirs in the upper crust are not interconnected. Key Points: The 3‐D seismic modeling shows the structure of the plumbing systems beneath the Avacha and Koryaksky volcanoes Beneath Avacha, a high Vp/Vs conduit connects a 2‐km‐deep magma chamber to the crater Beneath Koryaksky, the top of the magma chamber is visible at a depth of 7 km below the surface